PERANAN LOKASI DAN PELAYANAN TERHADAP LOYALITAS NASABAH PADA PD. BANK PASAR BOYOLALI - Sujadi, Sujadi; Nasir, Moechamad (Benefit: Jurnal Manajemen dan Bisnis, 2008)
This research is executed as a mean to identify, analysing and giving empirical evidence hit theinfluence of variable of location and variable of service PD. BPR Market Bank. to loyalty of client. The research also intended to identify the dominant variables affecting loyalty of client. As according to research hence this research is executed by using method survey, that is research taking sample from a population and use the questioner as a means of fundamental data compiler. Sampling technique utilized in this research is by random sampling that is by assuming each; every subject of existing in population got the opportunity the same chance to be selected to become the sample. The result of this research that, location PD. BPR Market Bank in the reality is not significant to loyalty of client PD. BPR Market Bank. While service given by PD. BPR Market Bank in the reality has the influence which are positive